Investigation and control of two consecutive Serratia marcescens outbreaks linked to reusable LigaSure devices in an operating room - Mahsa Mazaheri Tirani; Samaneh Pourajam; Vajihe Sadat Nikbin; Mohammad Shirzadi; Hamid Solgi (Antimicrobial Resistance and Infection Control)
Abstract Background Serratia marcescens is an opportunistic gram-negative bacterium that is commonly associated with sudden outbreaks of various healthcare-associated infections in healthcare settings. This study describes two consecutive mini-outbreaks of S. marcescens in an operating room following laparoscopic sleeve gastrectomy procedures. Methods Between December 16 and 26, 2020, five patients who underwent sleeve gastrectomy at a university hospital were re-admitted with clinical symptoms. An investigation by the infection control team was conducted to identify the source. Environmental and instrument samples were collected, and antimicrobial susceptibility testing was performed. Molecular typing using pulsed-field gel electrophoresis (PFGE) was conducted to assess the genetic relatedness of the isolates. Infection control interventions were implemented during the outbreak. Findings During this period, four of the five patients tested positive for S. marcescens. A total of 31 surveillance samples were collected, isolates from the handle of one LigaSure and the grasper of another were also positive for S. marcescens. PFGE revealed two distinct clones, indicating two separate outbreaks. Four of the six isolates from samples of patients and environment were the same, while two isolates belonging to another clone were collected from the blood samples of patients. After discontinuation of the reused LigaSure devices and implementation of strict infection control measures, no new cases were reported. Conclusion The two consecutive S. marcescens outbreaks were linked to the reuse of inadequately sterilized LigaSure devices. The implementation of targeted infection control measures successfully halted further transmission.